A low level of NaCl stimulates plant growth by improving carbon and sulfur assimilation in Arabidopsis thaliana - Li, Hongqiao; Suyama, Akiko; Mitani-Ueno, Namiki; Hell, Rüdiger; Maruyama-Nakashita, Akiko (Plants, 2021)
High-salinity stress represses plant growth by inhibiting various metabolic processes. In contrast to the well-studied mechanisms mediating tolerance to high levels of salt, the effects of low levels of salts have not been well studied. In this study, we examined the growth of Arabidopsis thaliana plants under different NaCl concentrations. Interestingly, both shoot and root biomass increased in the presence of 5 mM NaCl, whereas more than 10 mM NaCl decreased plant biomass. To clarify the biological mechanism by which a low level of NaCl stimulated plant growth, we analyzed element accumulation in plants grown under different NaCl concentrations. In addition to the Na and Cl contents, C, S, Zn, and Cu contents were increased under 5 mM NaCl in shoots; this was not observed at higher NaCl concentrations. Adverse effects of high salinity, such as decreased levels of nitrate, phosphate, sulfate, and some cations, did not occur in the presence of 5 mM NaCl. An increase in C was possibly attributed to increased photosynthesis supported by Cl, Zn, and Cu, which also increased in shoots after NaCl application. Salt stress-responsive gene expression was enhanced under 20 mM NaCl but not at lower doses. Among the S metabolites analyzed, cysteine (Cys) was increased by 5 mM NaCl, suggesting that S assimilation was promoted by this dose of NaCl. These results indicate the usefulness of NaCl for plant growth stimulation.